Adventure (Schooner) permit and manifest - Adventure (Schooner)
Permit and manifest of the cargo of the schooner Adventure sailing between Baltimore, Md., and New York, N.Y., with Richard Coward as master.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Coward, Richard; Ship's papers -- 18th century